Similar yet different: co-analysis of the genetic diversity and structure of an invasive nematode parasite and its invasive mammalian host. Issue 3 (March 2018) - Osten-Sacken, Natalia; Heddergott, Mike; Schleimer, Anna; Anheyer-Behmenburg, Helena E.; Runge, Martin; Horsburgh, Gavin J.; Camp, Lauren; Nadler, Steven A.; Frantz, Alain C.
Graphical abstract: Highlights: Parallel genetic analysis of an invasive host and its parasite in their new range was performed. The landscape genetic structure of a parasite and its host at a regional scale was analysed. There was evidence for extreme genetic diversity loss in the parasite. The landscape genetic structure of the parasite mirrored that of its host. Abstract: Animal parasitic nematodes can cause serious diseases and their emergence in new areas can be an issue of major concern for biodiversity conservation and human health. Their ability to adapt to new environments and hosts is likely to be affected by their degree of genetic diversity, with gene flow between distinct populations counteracting genetic drift and increasing effective population size. The raccoon roundworm ( Baylisascaris procyonis ), a gastrointestinal parasite of the raccoon ( Procyon lotor ), has increased its global geographic range after being translocated with its host. The raccoon has been introduced multiple times to Germany, but not all its populations are infected with the parasite. While fewer introduced individuals may have led to reduced diversity in the parasite, admixture between different founder populations may have counteracted genetic drift and bottlenecks. Here, we analyse the population genetic structure of the roundworm and its raccoon host at the intersection of distinct raccoon populations infected with B. procyonis . We found evidence for two parasite clusters resulting from independent introductions. Both clusters exhibited an extremely low genetic diversity, suggesting small founding populations subjected to inbreeding and genetic drift with no, or very limited, genetic influx from population admixture. Comparison of the population genetic structures of both host and parasite suggested that the parasite spread to an uninfected raccoon founder population. On the other hand, an almost perfect match between cluster boundaries also suggested that the population genetic structure of B. procyonis has remained stable since its introduction, mirroring that of its raccoon host.